Influence of organizational culture on employee performance through organizational citizenship behaviour as an intervening variable at the Sidoarjo Regency Regional Personnel Agency (Bkd) - Fiorentino, Kevin; Mujanah, Siti; Fianto, Achmad Yanu Alif (Indonesia Auditing Research Journal, 2024)
The purpose of this study is to determine the effect of organizational culture on employee performance, to determine the effect of organizational citizenship behavior on employee performance, and to determine the effect of organizational culture on employee performance through organizational citizenship behavior as an intervening variable. In this study, a quantitative approach was used because the data collected were in the form of numbers and the analysis was carried out using statistical methods. Sampling techniques are generally randomized, and data collection uses research instruments. The sample in this study were employees of the Sidoarjo Regional Staffing Agency totaling 15 respondents, taken from some employees. The results showed that organizational culture affects employee performance, OCB affects employees, and organizational culture affects employee performance through OCB as an intervening variable.